Affirmative Action HAM dalam Pemberdayaan Perempuan di Papua - Elmas Yuliantri; Faisal Akbar Nasution; Mirza Nasution; Sutiarnoto Sutiarnoto (Iuris Studia: Jurnal Kajian Hukum, 2021)
Article 28H, paragraph 2 of the 1945 Institution states that “Every person shall have the right to receive facilitation and special treatment to have the same opportunity and benegit in order to achieve equality and fairness.” Therefore, affirmative action can be used for a certain group of peopke that needs special treatment and facility.Law No.21/2001 on Special Autonomu for Papua is the Indonesian commitment to give new perspective in handling any probnlem in Papua by changing problem solving approach from security/stability approach to social/welfare approach. The realization of affirmative action can be seen from the establishment MRP (Papua People’s Assembly) as the culture representation of native Papua. It is the only State’s institution in Indonesia.Law on Special Autonomy gives the opportunity for Papua women to develop their self and position them as equal partners of men. Women’s active role in MRP is needed beacause in Papua women are still challenging against the social system and structure in the development so that they represent education and healt and Papua women empowerment fractions to realize the increase in the access ti and active role in development